Who is who? Competing coalitions in climate-AFOLU politics in Argentina_AnnexII_SupplementalMaterial - Luciana Apaza Laguna (22674800) (2025)
Annex II (supplemental material) for the article "Who is who? Competing coalitions in climate-AFOLU politics in Argentina, article per review. Author: Daniel Ryan and Luciana Apaza Laguna